Prioritizing Watersheds for Flood Risk Assessment in Uttarakhand Himalayas using Geospatial Techniques and TOPSIS Method - Kumar, Abhishek; Kumar, Pardeep (Acta Geographica Debrecina Landscape & Environment series, 2025)
Uttarakhand has a highly diverse topography, with snow-covered peaks, deep canyons, roaring streams, and dusty plains, all drained by various rivers of the Ganges system, India. The present study prioritizes watersheds in the Uttarakhand Himalayas for flood susceptibility using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method, supported by GIS and remote sensing data. ALOS PALSAR Digital Elevation Model (DEM) with 12.5-meter resolution was utilized to map topographic features and to analyze 18 morphometric parameters of 28 watersheds. The TOPSIS method prioritized sub-watersheds using AHP criteria weights, which are classified into five priority levels ranging from very low to very high. The Sarju, Ram Ganga, and Song watersheds were identified as having the highest flood risk, placing them in the “Very High” priority class. These watersheds exhibited high drainage density (Dd), stream frequency (Fs), and bifurcation ratio (Rb), indicating a dense and complex drainage network prone to rapid runoff and increased flood potential. The watersheds such as Bandagarh, Parry, and Chandra Bhaga were placed in the “Very Low” priority class due to lower closeness coefficient (Cci) values, suggesting simpler drainage systems and reduced flood risk. The AUC (Area Under Curve) value of 0.789, indicates a good predictive accuracy for the TOPSIS model. The classification helps in pinpointing high-risk areas that require urgent flood management interventions.